"An autobiography in which I do not appear": The Seductive Self in the Poetry of Robert Kroetsch. Issue 5 (3rd July 2016) - Korkka, Janne; Kokkola, Lydia; Valovirta, Elina
ABSTRACT: The article discusses selected works by the Western Canadian writer Robert Kroetsch (1927–2011) within the context of the biography battles which peaked during the 1990s. Kroetsch played a critical role in the formation and honing of a distinctive Prairie literary tradition in Canada, and we discuss a series of his poetic and other works published from the 1970s to 2010 which resonate with concerns raised within life-writing and life-writing criticism in the nineties. We focus on the almost obsessive concern with the relationships between self and other, and the seemingly contradictory denial of a stable self which mark the life writing debate of the decade; both evident in all of Kroetsch's writing. Raising the relation between space and selfhood to the fore, the article argues that Kroetsch's work not only questions our ability to know another through writing, but even to know the self. At the same time, we argue that the glimpses of a seemingly stable, autobiographical self that emerge in his writings speak to the seductiveness of gaining insights into the machinations of another person's mind, tempting Kroetsch again and again to ponder writing "an autobiography in which I do not appear".